Solusi Atas Problematika Perilaku Budgetary Slack Ditinjau Berdasarkan Etika Akuntan Manajemen - Muria, Rahadias Danar (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p17, 2020)
This article objective to find solution for the problematic of budgetary slack behavior based on management accountant ethics. This article examines the problem of budgetary slack and then connecting with management accountant ethics and ends with the preventive solution.  This research using qualitative approach with descriptive methods. This article finds that if it's related to management accountant ethics, sanctions for violating the principles of integrity, objectivity, confidentiality, and professionalism are by reducing the annual bonus, rotating positions, demoting positions, and the most extreme by dismissing the employee. Prevention efforts can be done by improving the ethical work climate. While, the violation of the competency principle is by giving warning letter with sanctions for reducing the annual bonus and rotating positions in other divisions. Prevention efforts can be done are providing education and training to improve the competence of the accountants. Keywords: Solution; Budgetary Slack; Management Accountant Ethics.